2010
DOI: 10.54648/eerr2010002
|View full text |Cite
|
Sign up to set email alerts
|

EU Foreign Policy Cooperation: A Challenge for National Parliaments?

Abstract: Abstract. European cooperation in the foreign policy domain is changing decision making in a broad number of issues. The analysis of the action taken by two legislatures – the British and the Italian Parliaments – as regards two foreign policy initiatives – the EU/E3 negotiations with Iran and the debate over lifting the European Union (EU) arms embargo against China – provides important insights on the strategies adopted by national legislatures to deal with cooperation in this field. The analysis confirms th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Zanon found that parliamentary scrutiny failed to address relevant questions in both cases and that political parties were using these issues only for rhetorical reasons (Zanon, 2007). In another study, the UK parliament was examined alongside the Italian parliament: the study found that MPs wished to control their governments but they also ‘realize[d] that any such move could weaken the ability of the government to conduct successful negotiations’ (Zanon, 2010, p. 36). More recent studies have emphasized that parties in opposition tended to initiate more scrutiny in order to decrease information asymmetry vis‐à‐vis the governments while coalition partners used the same instrument to control their partners (Herbel, 2017).…”
Section: Which Parliament(s) To Examine? Academic Perspectives On Tra...mentioning
confidence: 99%
“…Zanon found that parliamentary scrutiny failed to address relevant questions in both cases and that political parties were using these issues only for rhetorical reasons (Zanon, 2007). In another study, the UK parliament was examined alongside the Italian parliament: the study found that MPs wished to control their governments but they also ‘realize[d] that any such move could weaken the ability of the government to conduct successful negotiations’ (Zanon, 2010, p. 36). More recent studies have emphasized that parties in opposition tended to initiate more scrutiny in order to decrease information asymmetry vis‐à‐vis the governments while coalition partners used the same instrument to control their partners (Herbel, 2017).…”
Section: Which Parliament(s) To Examine? Academic Perspectives On Tra...mentioning
confidence: 99%